The Artificial Boundary Condition for Exterior Oseen Equation in 2-D Space (Journal of Computational Mathematics, 2021)
A finite element method for the solution of Oseen equation in exterior domain is proposed. In this method, a circular artificial boundary is introduced to make the computational domain finite. Then, the exact relation between the normal stress and the prescribed velocity field on the artificial boundary can be obtained analytically. This relation can serve as an boundary condition for the boundary value problem defined on the finite domain bounded by the artificial boundary. Numerical experiment is presented to demonstrate the performance of the method.
Keywords: Artificial boundary; Exterior domain; Oseen equation.